Manajemen Pembentukan Karakter Gotong Royong Untuk Meningkatkan Mutu Pendidikan Di SDN Golo Umbulharjo Yogyakarta - Julianti, Lisa; Purnami, Agustina Sri (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the management of character-building focused on mutual cooperation (gotong royong) in improving the quality of education at SD Negeri Golo. The research focuses on: (1) managerial processes including planning, organizing, implementation, control, and evaluation; (2) supporting and inhibiting factors as well as innovative solutions in fostering gotong royong character; and (3) the contribution of character management to improving education quality. A qualitative descriptive approach was employed, involving the school principal, teachers, students, and the school committee as research subjects. Data collection techniques included interviews, observation, and documentation, with data analysis comprising data reduction, presentation, and conclusion drawing. The findings reveal that the management of gotong royong character-building was carried out systematically through: (a) planning aligned with the school’s vision and mission, (b) the formation of an implementation team, (c) habituation-based implementation and guidance, and (d) evaluation and control by the school principal. Key supporting factors included school community enthusiasm and the principal’s motivational leadership. Innovative efforts encompassed internal-external collaboration, teacher training, practice-based approaches, and an integrative planning system. The gotong royong character management proved to contribute positively to creating a conducive school environment and significantly enhancing the overall quality of education.